Perputaran Persediaan dan Pertumbuhan Penjualan: Pengaruh terhadap Profitabilitas - Rahmaniar Rahmaniar (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to investigate the impact of inventory turnover and sales growth on profitability in cigarette companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. Additionally, the study seeks to evaluate the combined effect of inventory turnover and sales growth on the profitability of these cigarette companies during the same period. The analytical methods employed in this research include a descriptive approach and multiple linear regression analysis. The results indicate that inventory turnover has a significant impact on profitability, with a positive coefficient showing that an increase in inventory turnover is associated with increased profitability. Conversely, sales growth does not show a significant impact on profitability in this model. This suggests that sales growth is not a primary factor affecting profitability, as rising costs associated with sales growth may diminish its positive impact on profitability.